Icebergs versus Tariffs: A Quantitative Perspective on the Gains from Trade - Gabriel J. Felbermayr; Benjamin Jung; Mario Larch (Center for Economic Studies and ifo Institute (CESifo), 2013)
Recent quantitative trade models treat import tariffs as pure cost shifters so that their effects are similar to iceberg trade costs. We introduce revenue-generating import tariffs, which act as demand shifters, into the framework of Arkolakis, Costinot and Rodriguez-Clare (2012), and generalize their gains from trade equation. Our formula permits easy quantification based on countries observed degrees of openness, tariff revenues, and on the gravity elasticities of tariffs and icebergs. Export selection drives a wedge between these two elasticities and matters for welfare gains. However, in all model variants, an analysis based on iceberg costs necessarily underestimates the true gains from trade relative to autarky. Our quantitative exercise suggests that the bias can be numerically significant. For countries with relatively high tariffs, our formula predicts 30-60% larger gains from trade when iceberg trade costs and/or tariffs are liberalized as compared to a pure reduction of iceberg trade costs.
Keywords: F10; F11; F12; 330; gravity equation; monopolistic competition; heterogeneous firms; Armington model; international trade; trade policy; gains from trade